Factor allocation, economic growth and unbalanced regional development in China. (29th September 2017) - Liu, Guanchun; Liu, Yuanyuan; Zhang, Chengsi
Abstract: On the basis of development accounting techniques and a factor misallocation framework, we use panel data of 30 Chinese provinces from 2000 to 2013 to assess how factor allocation affects economic growth and unbalanced regional development in China. In particular, we decompose economic growth into three parts, namely sector productivity (SP), factor market efficiency (FME) and factor endowment (FE). We then conduct counterfactual analyses to investigate the short and long‐run roles of factor allocation in the income distribution across provinces. The results show that SP, FME and FE can explain 23%, 8.5% and 68.5% of economic growth, while labour, capital and energy reallocation account for aggregate productivity growth of about 47%, −4.8% and −0.1%. Furthermore, when the factors are efficiently allocated, transferring labour (capital, energy) from agriculture (service, industry) to the other sectors will increase the income per capita by 29.5% and 42.5% in the short and long term. Meanwhile, efficient factor allocation accounts for 32% and 29.7% of aggregate productivity and reduces the income variation across provinces by 25.5% and 23% in the short and long run, respectively.